School Memories. New Trends in the History of Education, por Cristina Yanes-Cabrera; Juri Meda; Antonio Viñao (editores). Cham, Springer, 2017, 278 pp. ISBN: 978-3-319-44062-0 - Collelldemont Pujadas, Eulàlia; Padrós Tuneu, Núria (Historia y Memoria de la Educación, 2017)
Review of the book:Yanes-Cabrera, Cristina; Meda, Juri and Viñao, Antonio (eds.), School Memories. New Trends in the History of Education (Cham: Springer, 2017)